P707 Using urgent small bowel ultrasound (SBUS) as a tool for decision-making in patients with inflammatory bowel disease (IBD): retrospective analysis of United Kingdom (UK) patients' outcome. (30th January 2023) - Lehmann, A; Nandra, G; Power, N; Lindsay, J O; ,
Abstract: Background: In the UK, magnetic resonance enterography (MRE) and colonoscopy are the gold standard assessment for mucosal disease activity in IBD. Both techniques require bowel preparation, may be poorly tolerated and are often subject to delay due to capacity issues. In several European centres, ultrasound is used as an alternative tool for disease activity monitoring and clinical decision-making. Recent studies confirm excellent sensitivity, specificity, correlation with MRE / colonoscopy and robust inter-observer agreement. In the UK, a lack of US training in IBD physicians has hindered development of accessible SBUS. In view of issues with MRI capacity during the covid pandemic, a dedicated small bowel ultrasound list with a gastroenterology fellow and a specialist radiology consultant for urgent IBD patients was initiated. Methods: Records of IBD patients undergoing SBUS between June 2022 and November 2022 were reviewed. SBUS assessed disease activity (vascularity, bowel wall thickness, mesenteric fat and lymphnodes), length of disease, presence of obstruction or fistulating disease. Patients were then retrospectively asked to rate their SBUS experience compared to previous MREs. Results: 53 SBUS's (46 (86.7%) CD; 2 (3.7%) UC) were performed on a dedicated SBUS list by a gastroenterology fellow and specialist radiology consultant during the study. In 29 patients (54.7%), the area of interest was the terminal ileum. SBUS detected disease complications in 7 (2 (3.7%) patients with obstructive disease, and 5 (9.4%)) patients with penetrating disease. The average waiting time from the point of referral to SBUS was 4.7 weeks, compared to an average waiting time for MRE of 20 weeks. Treatment response was assessed in 18 patients (33.9%). We were able to make treatment decisions with 32 patients (60.3%) based on their SBUS results without further assessment. In 10 patients (18.8%), SBUS was used to confirm a diagnosis in addition to colonoscopy. 18/22 ( 81%) patients reported a preference for SBUS compared to MRE (preference score of 4.5 on scale of 1-5). Conclusion: We developed an urgent SBUS service to aid timely clinical decision-making for IBD patients. In our practice, SBUS is an accurate tool to assess disease activity, significantly reduces patients waiting times and is the patient's preferred investigation. There is a clear unmet need to train IBD doctors and radiologists in SBUS.